Knowing My World: An English Learning Module Development with Multimodality and Deep Learning Approach - Haiyudi Haiyudi; Iful Rahmawati Mega; Dewi Agustin; Nurul Qomariyah; Zahra Herani; Sitthipon Art-in (Fenomena, 2025)
The new policy of the Indonesian educational system aims to engage all stakeholders, including teachers, in continually improving their capacity and adapting to changes. This study aims to develop an English language learning module titled "Knowing My World" for lower-grade primary students by adopting the ADDIE development model. The module integrates deep learning principles and local cultural content to enhance student engagement and contextual understanding, a development that has never been attempted before. This research was conducted at SDN 1 Kepulauan Pongok using a Research and Development (R&D) approach. The needs analysis revealed that students aged 8 to 9 years required visually rich, interactive, and culturally relevant materials. The design phase focused on structuring the module into six thematic units covering vocabulary related to colours, animals, food, daily routines, school, and nature. Instructional strategies included storytelling, songs, role-play, and group tasks. The module was piloted in one school, supported by teacher training and digital tools. The validity and practicality tests showed a valid result, with an average validity of 80.4% and an average practicality of 83% from both teachers and students. Suggestions for improvement included adding digital interactivity, bilingual guidance, and phonics-based activities. The results indicate that culturally contextualized and developmentally appropriate materials can support joyful and meaningful English learning in early education settings. Kebijakan baru dalam sistem pendidikan di Indonesia menuntut seluruh pemangku kepentingan, termasuk para guru, untuk terus meningkatkan kapasitas mereka dan beradaptasi dengan perubahan yang terjadi. Penelitian ini bertujuan untuk mengembangkan modul pembelajaran Bahasa Inggris berjudul “Knowing My World” bagi siswa sekolah dasar kelas rendah dengan menggunakan model pengembangan ADDIE. Modul ini mengintegrasikan prinsip pembelajaran mendalam serta muatan budaya lokal untuk meningkatkan keterlibatan siswa dan pemahaman kontekstual yang belum pernah dikembangkan oleh peneliti sebelumnya. Penelitian dilaksanakan di SDN 1 Kepulauan Pongok dengan pendekatan Research and Development (R&D). Hasil analisis kebutuhan menunjukkan bahwa siswa berusia 8–9 tahun memerlukan materi yang kaya visual, interaktif, serta relevan dengan budaya mereka. Pada tahap perancangan, modul disusun ke dalam enam unit tematik yang mencakup kosakata tentang warna, hewan, makanan, rutinitas sehari-hari, sekolah, dan alam. Strategi pembelajaran yang digunakan meliputi bercerita, lagu, bermain peran, dan tugas kelompok. Modul ini diujicobakan di satu sekolah dengan dukungan pelatihan guru dan pemanfaatan perangkat digital. Hasil uji validitas dan praktikalitas menunjukkan hasil yang baik, yaitu valid dengan persentase 80,4% pada uji validitas dan 83% pada uji praktikalitas rata-rata dari guru dan siswa. Beberapa saran perbaikan mencakup penambahan interaktivitas digital, panduan dwibahasa, serta kegiatan berbasis fonik. Hasil penelitian ini menunjukkan bahwa materi pembelajaran yang kontekstual secara budaya dan sesuai dengan tahap perkembangan anak dapat mendukung pembelajaran Bahasa Inggris yang menyenangkan dan bermakna di pendidikan dasar.